2017
DOI: 10.1089/hs.2016.0044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunoassays and General Biological Indicator Tests for Field Screening ofBacillus anthracisand Ricin

Abstract: There is little published data on the performance of biological indicator tests and immunoassays that could be used by first responders to determine if a suspicious powder contains a potential biothreat agent. We evaluated a range of biological indicator tests, including 3 protein tests, 2 ATP tests, 1 DNA test, and 1 FTIR spectroscopy instrument for their ability to screen suspicious powders for Bacillus anthracis (B. anthracis) spores and ricin. We also evaluated 12 immunoassays (mostly lateral flow immunoas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
0
20
0
2
Order By: Relevance
“…The sample preparation time is variable depending on the type of sample matrix and this will add more time to any assay. The CANARY ® Zephyr system is also portable, deployable to potentially manufacturing or processing centers because it consists of a laptop, a small centrifuge, and a small luminometer that can fit in a suitcase but still fit on a small bench top space [ 33 ]. Yet, its portability does not sacrifice utility, as the assay also uses small volumes (50 μL) to facilitate multiple sample analysis for precious samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample preparation time is variable depending on the type of sample matrix and this will add more time to any assay. The CANARY ® Zephyr system is also portable, deployable to potentially manufacturing or processing centers because it consists of a laptop, a small centrifuge, and a small luminometer that can fit in a suitcase but still fit on a small bench top space [ 33 ]. Yet, its portability does not sacrifice utility, as the assay also uses small volumes (50 μL) to facilitate multiple sample analysis for precious samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CANARY ® Zephyr system was evaluated against a variety of immunoassays (mostly lateral flow) as well as other biological indicator tests using the potential bioterror threats Bacillus anthracis and ricin. The study found that the limit of detection of ricin was 3.0 ng/mL and 10 3 spores/mL for B.anthracis [ 33 ]. The authors found that compared against various commercially available kits, the CANARY ® Zephyr platform was 4 orders of magnitude more sensitive for detecting B. anthracis and was the most sensitive for ricin.…”
Section: Introductionmentioning
confidence: 99%
“…This study has found that the assay is rapid: (< 40 min) from the addition of immunomagnetic capture beads to the reaction matrix to the read out of luminescence and final determination of positive or negative for the sample tested, which is better than most traditional methods. The CANARY ® Zephyr system is also portable, suitable for field-deployable because it consists of a laptop, a small centrifuge, and a small luminometer that can fit in a suitcase [33]. Yet, its portability does not sacrifice utility, as the assay also uses small volumes (50 μL) to facilitate multiple sample analysis for precious samples.…”
Section: Matrix Detection Limits (Ng)mentioning
confidence: 99%
“…Recently, the CANARY ® Zephyr system was evaluated against a variety of immunoassays (mostly lateral flow) as well as other biological indicator tests using the potential bioterror threats Bacillus anthracis and ricin. The study found that the limit of detection of ricin was 3 ng/mL and 10 3 spores/mL for B.anthracis [33]. The authors found that compared to all of the other commercially available kits, the CANARY ® Zephyr platform was 4 orders of magnitude more sensitive for detecting B. anthracis and was the most sensitive for ricin.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, metagenomic sequencing on second-generation sequencing technology typically requires more than a 24 hour time investment on non-portable machines. Consequently, field-forward biosurveillance has been limited to primarily PCR-based assays 19–21 or antibody hybridization technologies 2225 , which have been the first molecular biology hardware to reach a portable, hand-held form factor.…”
Section: Introductionmentioning
confidence: 99%